A Complicated Case of Acute Promyelocytic Leukemia in the Second Trimester of Pregnancy Successfully Treated with All-trans-Retinoic Acid - Kanika Agarwal; Megha Patel; Vandana Agarwal (Case Reports in Hematology)
A 40-year-old female at 26-week gestation was diagnosed with acute promyelocytic leukemia (APL) after an abnormal prenatal lab workup showed pancytopenia. She was treated with all-trans-retinoic acid (ATRA), idarubicin, and dexamethasone. After day one of treatment, she developed differentiation syndrome, which was treated with dexamethasone. At 30-week gestation, she had preterm premature rupture of membranes and delivered by cesarean section because of the fetus’ breech presentation. Despite ATRA’s potential for teratogenicity, a viable infant was born without apparent anomalies. Postpartum, she underwent consolidation treatment with ATRA and arsenic trioxide (ATO). The patient continued ATRA therapy after delivery and is currently in remission.